2018
DOI: 10.1103/physrevmaterials.2.073608
|View full text |Cite|
|
Sign up to set email alerts
|

Kink-limited Orowan strengthening explains the brittle to ductile transition of irradiated and unirradiated bcc metals

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…While the screw dislocation glide is well characterized in pure bcc materials [8,9], solutes can have a strong effect on the dislocation properties leading to hardening or softening of the material [10]. In tungsten Ir, Pt, Au, and Hg solute atoms show a strong attraction to screw dislocations resulting in hardening by a pinning mechanism, while Hf, Ta, and Re reduce glide barriers and thus facilitate plastic slip [11].…”
Section: Introductionmentioning
confidence: 99%
“…While the screw dislocation glide is well characterized in pure bcc materials [8,9], solutes can have a strong effect on the dislocation properties leading to hardening or softening of the material [10]. In tungsten Ir, Pt, Au, and Hg solute atoms show a strong attraction to screw dislocations resulting in hardening by a pinning mechanism, while Hf, Ta, and Re reduce glide barriers and thus facilitate plastic slip [11].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of the author's knowledge, there is currently no experimental technique enabling direct evaluation of dislocation population mobility, let alone their characteristic, dosedependent evolution. An atomic-scale model has been recently developed, however, explaining the brittle-ductile transition based on isolated dislocation/obstacle interaction cases [72]. This model confirms that defect-induced dislocation mobility evolutions can help revealing/evaluating the brittle-ductile transition evolutions.…”
Section: Grain Setups and Dislocation/defect Interaction Implementationmentioning
confidence: 58%
“…The main factor that determines the outcome in the competition between cleavage fracture and ductile tearing is the ability of the plastic deformation to relieve the applied stresses ahead of a crack. On a microstructural scale, plastic flow in bcc metals is controlled by the thermally activated movement of screw dislocations, which is dependent on a combination of an internal lattice resistance and an interaction between the dislocations and obstacles in the microstructure [ 5 , 6 , 7 ]. A recently published dislocation-obstacle model showed that the activation energy for plastic flow is mainly determined by the kink (which represents a step of atomic dimension in a dislocation line) formation energy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…On a microstructural scale, plastic flow in bcc metals is controlled by the thermally activated movement of screw dislocations, which is dependent on a combination of an internal lattice resistance and an interaction between the dislocations and obstacles in the microstructure [ 5 , 6 , 7 ]. A recently published dislocation-obstacle model showed that the activation energy for plastic flow is mainly determined by the kink (which represents a step of atomic dimension in a dislocation line) formation energy [ 7 ]. Swinburne and Dudarev [ 7 ] were able to predict the ductile to brittle transition temperature in both unirradiated and irradiated ferritic-martensitic steels, where the irradiated temperature increased up to twice that of the unirradiated material in agreement with multiple experimental data.…”
Section: Introductionmentioning
confidence: 99%